2020
DOI: 10.1177/0300060520949077
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the epidemiology, pathophysiology, diagnosis and management of SARS-CoV-2

Abstract: The emergence of coronavirus disease 2019 (COVID-19) in December 2019 has resulted in over 20 million cases and 741,808 deaths globally, affecting more than 200 countries. COVID-19 was declared a pandemic on 11 March 2020 by the World Health Organization. The disease is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). There is limited information on COVID-19, and treatment has so far focused on supportive care and use of repurposed drugs. COVID-19 can be transmitted via person-to-person … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 108 publications
0
25
0
1
Order By: Relevance
“…The step immediately after evaluating all the participants together was to investigate their perception of COVID-19 by considering their sociodemographic profiles and each research variable. Thus, each of the respondent's health education indicators was evaluated considering, for example, sex (male and female), education level (middle/high school and higher/postgraduate education), age (18-83 years), socioeconomic vulnerability (receiving or not receiving government support), and the number of people per residence (1)(2)(3)(4)(5)(6). These indicators were evaluated for their respective distributions for each profile (unpaired), and the odds ratios between the worst outcomes (lowest score) were compared with those between the best outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The step immediately after evaluating all the participants together was to investigate their perception of COVID-19 by considering their sociodemographic profiles and each research variable. Thus, each of the respondent's health education indicators was evaluated considering, for example, sex (male and female), education level (middle/high school and higher/postgraduate education), age (18-83 years), socioeconomic vulnerability (receiving or not receiving government support), and the number of people per residence (1)(2)(3)(4)(5)(6). These indicators were evaluated for their respective distributions for each profile (unpaired), and the odds ratios between the worst outcomes (lowest score) were compared with those between the best outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The disease does not yet have a vaccine or definitive treatment. For this reason, measures such as social distancing, proper hygiene, and the use of individual and collective protective equipment have been instituted by different health authorities, which have been shown to be central to preventing the transmission of the virus and controlling the spread of the disease [ 4 , 5 ]. In addition, knowledge about the infection and its signs and symptoms, whether by the general population or by health professionals, has also been shown to be effective in aiding early diagnosis, better monitoring, and more effective treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 is an extremely infectious virus, with a very rapid spread worldwide, being declared a global threat by the World Health Organization (WHO) and causing the most challenging pandemics of this century. SARS-CoV-2 is a RNA virus with a genetic structure, which is similar to that of SARS-CoV-1 and of Middle East respiratory syndrome (MERS) -CoV [ 1 ].…”
Section: Pathogenesis Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…This is reported that 80% of affected cases are moderate, with typical fever and flu, so patients will recover at home. In brief, a patient with leukopenia or lymphopenia will be accused of developing upper respiratory tract symptoms and fever [52][53][54][55][56].…”
Section: Symptoms Of Covid-19mentioning
confidence: 99%